A Pan-Cancer Analysis of IRAK1 Expression and Their Association With Immunotherapy Response - Liu, Mengmeng; Que, Yi; Hong, Ye; Zhang, Lian; Zhang, Xing; Zhang, Yizhuo (Frontiers in Molecular Biosciences, 2022)
IRAK1 is an active kinase which plays a critical role in IL-1/TLR signaling pathway involved in inflammation and innate immune response. Recently, increasing evidence supports a potential role of IRAK1 in cancer progression. However, no immunological pan-cancer analysis of IRAK1 is available. We aimed to explore the prognostic value and the immunological functions of IRAK1. A serious of datasets including The Cancer Genome Atlas, GEPIA2, cBioPortal, HPA, TIMER2.0 were performed to explore the oncogenic and immunological roles of IRAK1, including the relationship between IRAK1 and prognosis, genetic mutation, GO and KEGG enrichment pathway analysis, immune state of different tumors. The results showed that IRAK1 levels were upregulated in more than 20 types of cancers compared to the normal tissues. IRAK1 expression was associated with poorer prognosis in different cancer types. The most frequent DNA alteration of IRAK1 is amplification. The result of the enrichment analysis suggested that IRAK1 related to immune checkpoint pathway in cancer. IRAK1 inhibitor pacritinib inhibit proliferation and upregulate PD-L1 expression in different cancer cell lines. Moreover, the patients who receiving anti-PD-L1 therapy with low IRAK1 expression had a better prognosis, and the objective response rate to anti-PD-L1 therapy was higher in the low IRAK1 group than in the high IRAK1 group in IMvigor210 cohort. Our study reveals that IRAK1 can function as a prognostic marker in various malignant tumors. And pacritinib upregulated PD-L1 expression in several cancer cell lines, which indicating that IRAK1 can be used as a reliable marker to predict the efficacy of immunotherapy.